Developing Positive Attitude Towards Self - Amanda Narda Mutia; Teta Pamungkas Sari; Della Juana Sukma; Ilil Maidah; Betty Wulan Safitri (International Conference on Psychology and Education (ICPE), 2023)
Humans are dynamic creatures that change constantly over time. Basically, human beings have always evolved to evolve into better direction to be an ideal individual. Many aspects humans can develop are aspects of attitude. Positive attitudes of themselves are among the characteristics of a mood as a determiner of a person's success in a process. Positive attitude itself is one of the properties of a mood as a determiner of a person's success in a process. As for a positive attitude pertaining to some aspect, it includes honesty, responsibility, caring, courtesy, and confidence. This attitude is also important to apply to today's life because it is very relevant as the foundation for taking appropriate action in accordance with the current situation and circumstances and as a foundation for the expected character formation. The study aims to further examine how to develop positive attitudes and positive effects on individuals. The research methods used are qualitative with literature study techniques. It was found that in developing a positive attitude, the effort can be made by changing habits, using technique for problem solving, and providing social counseling guidance.